2019
DOI: 10.4103/njms.njms_49_18
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of two-point fixation in the management of zygomatic complex fractures – A prospective clinical study

Abstract: Introduction:Anatomic disfigurement caused by zygomatic fracture warrants intervention tore establish facial symmetry. It is most predictably restored to pre morbid condition by ORIF.Aim:To evaluate the efficacy of 2 point fixation in Zygomaticomaxillary complex fractures.Material and Method:20 patients with established ZMC fractures were operated using two point fixation method and followed up for upto 3 months.Results:2 point fixation revealed satisfactory functional and esthetic results.Conclusion:2 point f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Another study on the stability of two-point fixation was conducted on 20 patients by Mittal et al by comparing the values of the malar height and vertical dystopia disparity in the water's view radiograph before and after the operation. The study demonstrated that radiographic and clinical indices significantly improved after surgery, demonstrating that two-point fixation successfully stabilizes the fragmented pieces [21] . The results of the present study agree with the conducted results above as clinically and aesthetically sufficient results were obtained after fixation of ZMC by the 2-point technique providing the reliability of using the 2-point technique for management of ZMC fractures.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Another study on the stability of two-point fixation was conducted on 20 patients by Mittal et al by comparing the values of the malar height and vertical dystopia disparity in the water's view radiograph before and after the operation. The study demonstrated that radiographic and clinical indices significantly improved after surgery, demonstrating that two-point fixation successfully stabilizes the fragmented pieces [21] . The results of the present study agree with the conducted results above as clinically and aesthetically sufficient results were obtained after fixation of ZMC by the 2-point technique providing the reliability of using the 2-point technique for management of ZMC fractures.…”
Section: Discussionmentioning
confidence: 81%
“…The identification, evaluation, and surgical treatment of ZMC fractures have been the subject of a great deal of research. Nevertheless, quantitative measurement of postoperative malar asymmetry has not been the basis of many studies [21][22][23] . Using paired landmarks, the asymmetry index may measure the three-dimensional face symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 20 patients with established ZMC fractures were operated with a two-point fixation method and followed up for up to 3 months. 2-point fixation revealed satisfactory functional and aesthetic results, offering an efficient result compared to other modalities of management of ZMC [24].…”
Section: Major Clinical Outcomesmentioning
confidence: 84%
“…Mittal et al in their study on pre and post operative values on vertical dystopia and malar height discrepancy showed a statistically significant increase in clinical parameters post operatively and concludes that 2-point fixation provides a stable fixation. 18 In our trauma center 2-point fixation was maximally used in 3 years. Acquiring an informed consent for performing infraorbital approach for reducing and fixing was bit tiresome as they were not prepared for scar below the eye as most of the patients were in young age group.…”
Section: Discussionmentioning
confidence: 99%